PENGARUH KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN PADA USAHA TUKANG KAYU DI UD. RULLIN DESA HILINDASONIHA - Laia, Kevin Samuel Sabatini; Sarumaha, Martiman Suaizisiwa (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
The aim of this research is to determine the effect of product quality on consumer buying interest at UD. Rullin Hilindasoniha Village. This type of quantitative research is causal in nature. The population in this research is UD consumers. Rullin Hilindasoniha Village, numbering 120 people. The research sample is 15% of the total population, namely 15% of 120 people, so the total research sample is 30 people. The research result is that the hypothesis is accepted with a value of t_count=5.292>t_tabel=2.048, which means that product quality influences consumer buying interest at UD. Rullin Hilindasoniha Village. The coefficient of determination test results were 56.73%, which means that the influence of product quality on consumer buying interest was 56.73% and the remainder was influenced by other factors apart from the variables of this research. The research conclusion is that consumers state that product quality is good when their needs and desires for the product can be satisfied. A product produced by a producer is valuable because of the value seen by consumers, because the value contained in a product will attract consumers' buying interest, and this value can be sourced from the quality of the product used. Researchers put forward suggestions, namely (1) For UD. Rullin Hilindasoniha Village should consider suggestions from consumers to further improve product quality and not disappoint consumers, so that consumers are satisfied and return to shopping. (2) It is hoped that future researchers will be able discuss issues regarding product quality and consumer buying interest more widely by adding appropriate independent variables so that they can further strengthen the current conversation with various aspects therein.